Characterization of Lentinula edodes Lectin: Effects of pH, Temperature, and Molecular Weight on Antifungal Activity (Journal of the College of Basic Education, 2026)
Lectin are characterized according to different methods like pH , temperature, molecular weight , different PH was taken in the range from (4_9) and the activity of lectin was determined by measuring the hemagglutination and different temperatures was taken to determine the lectin activity in the range (22,27,32,37 and 42 °C) in different durations (10,20,30) minutes and the molecular weight determination was done by gel filtration chromatography and the effects of different PH and temperatures on Candida spp. growth and lectin production by measuring the inhibition zones. The results of temperatures characteristics was shown have varying degrees of thermal stability the lectin activity peaked at 32(60.3)and the hemagglutination activity decrease with rising temperature and in PH the lectin activity peaked at PH 5(50.6) and the activity was decreased in PH (7,8,9) and the molecular weight of lectin was 100000.And the antifungal effectiveness of purified lectin against several spp. of Candida no inhibition was observed at very alkaline or extremely acidic PH values , lectin activity increase gradually from 22 to peak between 32 and37 and declined at 42 °C.